2016
DOI: 10.1200/jco.2016.66.7311
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Metastatic Renal Cell Carcinoma: Clinical and Biological Correlations

Abstract: Obesity is an established risk factor for clear cell renal cell carcinoma (RCC); however, some reports suggest that RCC developing in obese patients may be more indolent. We investigated the clinical and biologic effect of body mass index (BMI) on treatment outcomes in patients with metastatic RCC. MethodsThe impact of BMI (high BMI: $ 25 kg/m 2 v low BMI: , 25 kg/m 2 ) on overall survival (OS) and treatment outcome with targeted therapy was investigated in 1,975 patients from the International Metastatic Rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
122
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 34 publications
15
122
2
Order By: Relevance
“…This phenomenon, wherein higher BMI is associated with increased disease risk but confers a survival advantage in patients with established or advanced disease, has recently been described in other malignancies. 79 Whether this inverse relationship is causal remains poorly understood. 10 However, several features of the current study suggest a potential biological role of adiposity in metastatic melanoma patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon, wherein higher BMI is associated with increased disease risk but confers a survival advantage in patients with established or advanced disease, has recently been described in other malignancies. 79 Whether this inverse relationship is causal remains poorly understood. 10 However, several features of the current study suggest a potential biological role of adiposity in metastatic melanoma patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in renal cell carcinoma in which high BMI was associated with improved outcomes with targeted therapy found that alterations in fatty acid metabolism were associated with both obesity and outcomes. 9 Given emerging evidence implicating tumor and immune cell metabolism in melanoma therapeutic response, 25 the relationship between tumor metabolism and clinical metabolic phenotype should also be explored in this disease. Analyses are ongoing examining the molecular, immunologic, and metabolic correlates of obesity in melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hakimi et al reported that high BMI was associated with reduced RCC stage at diagnosis and improved survival on univariate analysis; however, high BMI had no relationship with cancer-specific mortality after stage and grade were controlled [21]. Albiges et al compared survival in over 5,000 subjects with metastatic RCC, and found that high BMI (BMI > 25 kg/m 2 , including both overweight and obese subjects) was associated with increased OS following targeted therapy [22]. These and other findings have led to the conclusion that an obesity paradox exists for RCC, wherein obesity defined by high BMI is associated with less advanced disease and better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of metastatic RCC patients demonstrated a positive association between excess body weight and a longer overall survival, which may be due to a decreased expression of the fatty acid synthase ( FASN ) gene in obese patients [20]. As adipose tissue is composed of fatty acids, the decreased expression of FASN is likely to influence the production of adipokines and other obesity-related markers in RCC patients and could be one of the mechanisms through which carcinogenesis occurs.…”
Section: Discussionmentioning
confidence: 99%